High voltage GaN‐on‐silicon HEMT. Issue 5 (27th March 2013) - Boles, T.; Varmazis, C.; Carlson, D.; Palacios, T.; Turner, G. W.; Molnar, R. J.; Krishna, Sanjay; Plis, Elena
Abstract M/A‐COM Technology Solutions has continued in the joint development efforts sponsored by the Department of Energy with MIT main campus and MIT Lincoln Labs to develop GaN on silicon three terminal high voltage/high current HEMT switching devices. The first year developmental goals were for a three terminal structure that has a reverse breakdown characteristic of >1200 V and is capable of switching 10 amperes of current. An average three terminal breakdown of 1322 V was achieved on a single finger 250 µm GaN on silicon HEMT device utilizing a source connected field plate with a 4.5 µm drain region overlap. An individual device breakdown on a single finger 250 µm GaN on silicon HEMT device with a SCFP of >1630 V was measured at a current of 250 µA (1mA/mm) – One of the highest yet reported for GaN on silicon in the industry. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)